The Impact of Increasing Toll Shop Automation on Income Tax with Vehicle Volume as a Moderatting Variable - Irma Yunita; Enjat Sudrajat (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to determine the impact of increasing the automation of toll booths on income tax with vehicle volume as a moderating variable. This research method uses the Sem PlS 3.0 method with secondary data obtained from the annual hassle of PT. Jasa Marga in 2009-2018. The result of the research is that automatic toll booths have a significant effect on income tax and vehicle volume while vehicle volume on income tax has no effect.